KAJIAN ETNOBOTANI TANAMAN OBAT TRADISIONAL OLEH MASYARAKAT DESA LAPPA UPANG KECAMATAN MARE KABUPATEN BONE SEBAGAI SUMBER BELAJAR ETNOBOTANI DALAM BENTUK MODUL - Hafsah, Hafsah; Hi Panu, Rasmi; Jasruddin, Jasruddin; Harlina, Harlina; Haeruddin, Hasriani (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2024)
Traditional medicine using plants has been carried out for generations by Indonesian people. Mare Region is a sub-district located in Bone Regency, South Sulawesi Province. One of the villages in Mare District is Lappa Upang Village. The people of Lappa Upang Village have knowledge about the use of surrounding plants as medicine for certain diseases or health problems. The research aims to: 1) obtain information on the types of plants used as medicine; 2) find out the types of use of medicinal plants by the people of Lappa Upang Village, Mare District, Bone Regency regarding the use of medicinal plants. This type of research is exploratory descriptive research. The method used in collecting data was an exploratory survey with direct observation in the field. Community involvement was obtained through interviews using semi-structural and open-ended interview techniques guided by a list of questions. The results of the research recorded that there were 23 types of plants that were used by the local community of Lappa Upang Village as ingredients for traditional medicine. These plants include: Soursop, guava, pariah, bay leaf, papaya, candlenut, yellow turmeric, black turmeric, shallots, garlic, ginger, red ginger, kencur, mango, pacci, purple sweet potato, coriander, sere, pissing-pissing, sugar cane, tempuyung, aria, cere cella. can be used as material in making an Ethnobotany module